1998
DOI: 10.1152/ajpcell.1998.275.1.c155
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy-stimulated myogenic regulatory factor mRNA increases are attenuated in fast muscle of aged quails

Abstract: Myogenic regulatory factors (MRFs) are a family of skeletal muscle-specific transcription factors that regulate the expression of several muscle genes. This study was designed to determine whether MRF transcripts were increased in hypertrophy-stimulated muscle of adult quails and whether equivalent increases occurred in muscles of older quails. Slow-tonic anterior latissimus dorsi and fast-twitch patagialis muscles of adult, middle-aged, aged, and senescent quails were stretch overloaded for 6, 24, or 72 h, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 37 publications
10
68
0
1
Order By: Relevance
“…In that context, we did not observe changes in VEGF, XRCC1, RANTES, or EGR-1 levels in response to ST. We did observe small increases in IL-1β with ST in young men and women, but not in older men and women, which is consistent with the acute exercise response reported by Jozsi et al (15). In summary, our data compare favorably to existing reports for comparable genes and extend the existing literature by providing the first investigation to examine skeletal muscle gene expression in relation to sex and chronic ST.Several genes that might be hypothesized to be differentially expressed as a result of age (11,16,19,21,25) could not be verified in the present study because they were not represented on the GF211 microarray (e.g., muscle transcription factors). Few of the genes shown in Supplementary Tables S3 and S4, genes differentially expressed in relation to age, are immediately recognizable as previously studied muscle-related genes, with GAPDH, carbonic anhydrase III, and tropomyosin-β being the most studied in skeletal muscle.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…In that context, we did not observe changes in VEGF, XRCC1, RANTES, or EGR-1 levels in response to ST. We did observe small increases in IL-1β with ST in young men and women, but not in older men and women, which is consistent with the acute exercise response reported by Jozsi et al (15). In summary, our data compare favorably to existing reports for comparable genes and extend the existing literature by providing the first investigation to examine skeletal muscle gene expression in relation to sex and chronic ST.Several genes that might be hypothesized to be differentially expressed as a result of age (11,16,19,21,25) could not be verified in the present study because they were not represented on the GF211 microarray (e.g., muscle transcription factors). Few of the genes shown in Supplementary Tables S3 and S4, genes differentially expressed in relation to age, are immediately recognizable as previously studied muscle-related genes, with GAPDH, carbonic anhydrase III, and tropomyosin-β being the most studied in skeletal muscle.…”
supporting
confidence: 60%
“…Several genes that might be hypothesized to be differentially expressed as a result of age (11,16,19,21,25) could not be verified in the present study because they were not represented on the GF211 microarray (e.g., muscle transcription factors). Few of the genes shown in Supplementary Tables S3 and S4, genes differentially expressed in relation to age, are immediately recognizable as previously studied muscle-related genes, with GAPDH, carbonic anhydrase III, and tropomyosin-β being the most studied in skeletal muscle.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 82%
See 1 more Smart Citation
“…There are several reports of MRF upregulation in response to various muscle perturbations including stretch overload (11,42), ablation (2, 3), denervation (35), myotoxicity (43), and acute resistance loading (9,22,34,53,61). In a number of these studies, MRF responses and/or muscle repair mechanisms were found to be limited by old age (34,(41)(42)(43)61). This may result from heightened basal levels of MRFs in the aging muscle (7,34,35,49) because MRF expression tends to increase as the degree of sarcopenia advances (17).…”
Section: Effects Of Age On Load-mediated Changes In Regenerative Markersmentioning
confidence: 99%
“…Therefore, events that initiate the hypertrophic response can be studied. 47 Chronic stretch has also been shown to induce hyperplasia (new muscle fiber formation); 5,7,9,16,35 thus the stretch model is valuable for studying mechanisms of new fiber formation. It should be noted that evidence for hyperplasia exists from several other animal hypertrophy models (reviewed by Kelley 41 ) and also after PRE in humans.…”
Section: Chronic Stretch Modelsmentioning
confidence: 99%